La cultura como instrumento de transformación urbana en la Ciudad Autónoma de Buenos Aires : el caso del Distrito de las Artes - Villarino, Julio (2023)
For fifteen years, the government of the Autonomous City of Buenos Aires has created seven economic districts, three of which are related to culture. In the case of the Arts district, it promotes visual, musical and performing arts. This district expands over an area - including the neighborhoods of La Boca and part of San Telmo, Barracas and Constitución - which shows signs of urban decay and a social housing deficit. The strategy carried out by the city government to requalify this area, generate economic development and stimulate the regeneration process is the creation of such district along with other urban and cultural interventions. This promotion policy - based on fiscal incentives - implies the attraction of real estate investments and new art activities that reject other popular and neighborhood cultural expressions. The establishment of distinguished and sophisticated art spaces contrasts with the critical social situation of large sectors of the area, harassed by evictions. Changes in land use and the increase of its value reveal an incipient gentrification process. Social and cultural actors express different points of view regarding the benefits of this urban regeneration and requalification process.